“GIVE ME A JOKE, PLEASE!”: CREATING A FUN LEARNING BY TEACHERS’ JOKES - Hibatullah, Oktari Firda; Ardlillah, Queen Fiqi (PEOPLE: International Journal of Social Sciences, 2019)
There are lot of phenomena that often happened in teaching and learning processes. One of them is the problems faced by the students in their learning processes. For instance, they are feeling demotivated, sleepy, and bored while the processes in classroom. In order to deal with the problems, some of teachers already had a strategy in their teaching process by doing jokes. However, not all of the jokes can resolve the students’ problem effectively. Furthermore, the impacts that the students got by the jokes were less investigated deeply by prior studies. Thus, the purposes of this study are knowing the certain jokes that affect the students’ learning process and exploring the impacts of the jokes towards the process. This study then narrows the learning process into a language learning process. A qualitative study is used as an approach of this study by conducting classroom observation and interview to collect the data. The data showed that there were several jokes that able to cope with the students’ problems, and several good impacts of the jokes found in the students’ language learning processes. To sum up, the teachers’ jokes can be a way to create a fun learning which encourages the students in their language learning processes.